PENGARUH RASIO EFEKTIVITAS PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA ALOKASI KHUSUS TERHADAP TINGKAT KEMANDIRIAN KEUANGAN DAERAH DI PROVINSI DIY - Achmad Tjahjono; Rika Oktavianti (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This research aim to reveal the influence of local own revenue effectivity ratio, general allocation fund, and special allocation fund to the local financial independence level on districts and city in Daerah Istimewa Yogyakarta. The method of this research is cauvative research design. Budget realization report from each districs and city in Daerah Istimewa Yogyakarta as population from the year 2010 to 2014. Techniques of data analysis using multiple linear regression. The Partial result show that local own revenue effectivity ratio did not significantly effect on the local financial independence level. While, general allocation fund, and special allocation fund impact negative significantly effect on the local financial independence level. The Simultaneously result show that local own revenue effectivity ratio, general allocation fund, and special allocation fund impact positive significantly to the local financial independence level.